Communication Between Teachers and Students in Increasing Learning Interest Reciting Al-Qur'an - Maharani, Tesya; Anggraini, Natasya Ziqra; Hanif, Akhyar (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2024)
This research is motivated by poor communication conducted by teachers to students by using harsh communication and using actions. This study aims to determine the dyadic and small group communication conducted by teachers to students in increasing interest in learning to read the Qur'an. This study uses a descriptive qualitative method to obtain broad and in-depth information related to the objectives of the study. The data sources in this study were teachers, students, and parents of students of TPQ/TQA Qosrul Qur'an. The results of the first study, teachers in increasing interest in learning to read the Qur'an can be categorized by the author into dyadic communication, namely dyadic communication in the form of conversation, dyadic communication in the form of dialogue and dyadic communication in the form of interviews. Second, teachers use small group communication, namely in the form of face-to-face and discussion. Dyadic communication is used by teachers when in the learning and teaching process, while small group communication is used when teachers discuss with parents and naughty students, and when learning to create new art and rhythm. Third, teachers in increasing interest in learning to read the Qur'an can be categorized by the author into factors that influence students' interest in learning to read the Qur'an, factors that influence interest in learning to read the Qur'an include supporting factors and inhibiting factors, the supporting factors are physical and spiritual health, psychological and the inhibiting factors are family, environment and school.